Instrument transducers - Neubert, Hermann K. P. (Oxford University Press, 1999)
Instruments Transducers' maintains the emphasis on transducers as entities with respect to physical principles, performance analysis, design, and construction Aspects of mechanical and electrical design procedures of specific materials, and of modern construction techniques are discussed in greater detail than available elsewhere, against the background of exacting performance requirements. The International System of Units (SI) is used throughout the text. The book is aimed at engineers active in the field of instrumentation and control engineering